Honoring the Good Parent Intentions of Courageous Parents: A Thematic Summary from a US-Based National Survey - Meaghann S. Weaver; Marie L. Neumann; Blyth Lord; Lori Wiener; Junghyae Lee; Pamela S. Hinds (Children, 2020)
Background: Parents of children with complex medical needs describe an internal, personal definition of “trying to be a good parent” for their loved child. Gaps exist in the current “good parent concept” literature: (1) When the idea of “trying to be a good parent” comes into existence for parents, (2) How parents’ definition of “being a good parent” may change over time and may influence interactions with the child, and (3) Whether parents perceive attainment of their personal definition. Aim: The purpose of this study was to explore these current gaps in the “good parent concept” knowledge base from the perspective of parents of children with chronic or complex illness. Materials and Methods: These themes were explored through a 63-item, mixed-method web-based survey distributed by the Courageous Parents Network (CPN), an organization and online platform that orients, educates, and empowers families and providers caring for seriously ill children. Results: The term “trying to be a good parent” resonated with 85% of the 67 responding parents. For the majority of parents, the concept of “being a good parent” started to exist in parental awareness before the child’s birth (70.2%) and evolved over time (67.5%) to include less judgment and more self-compassion. Parents identified their awareness of their child’s prognosis and changing health as influential on their “trying to be a good parent” concept. Parental advocacy, child’s age, and duration of illness were reported as influencing parental perceptions of having achieved their definition of “being a good parent”. Conclusions: Familiarity with parental perspectives on their parenting goodness and goals is a necessary core of family-centric health care.